UJI POTENSI UMBI KIMPUL (Xanthosoma sagittifolium (L.) Schott.) SEBAGAI BAHAN PANGAN FUNGSIONAL ANTIULSER PADA MENCIT (Mus musculus L.) - Triyani Yuliastuti; Marti Harini; Noor Soesanti Handajani; Tetri Widiyani (Metamorfosa: Journal of Biological Sciences, 2016)
Cocoyam (Xanthosoma sagittifolium (L.) Schott.) tuber is usually consumed as carbohydrates source. Because of highly mineral and fiber contents, it is potential to develop as a functional food source. The mineral contents are potassium, phosphor, magnesium, iron, copper and sodium. Some minerals are well known able to neutralize pH of the gastric fluid. It is necessary to study cocoyam activity on the ulcer gastric. The aims of this study were to determine anti-ulcerogenic activity of cocoyam tuber by observing macroscopic stomach mucous structure on mice and measuring the gastric fluid pH. Twenty male mice aged 2-3 months were used in this study. They were classified in to 4 different treatment groups. Group I was control mice without gastric ulcer, group II, III, and IV were mice with gastric ulcer by using aspirin treatment. Group II,III, and IV were treated with different treatments then for 7 days. Group II was treated by aquadest (negative control group), group III by sucralfat (positive control group), and group IV by cocoyam tuber. In the last treatment day, mice were fasted for 24 hours and then sacrified to pick stomach up. Gastric fluid was collected and the pH was measured then. Stomach mucous structure was observed macroscopically. Data in the gastric fluid pH was analyzed by using one-way ANOVA (Analysis of Variance) and continued  HSD (Honest Significant Difference)-Tukey test in 5% significance degree. Degree of stomach mucous structure damage was analyzed descriptively and then it was scored based on number and diameter size of ulcers. Data on the ulcer score were analyzed by using Kruskal-Wallis test. The results showed that there was a significant difference (p<0.05) at the stomach fluid pH. Normal group was not significantly different to the sucralfat and cocoyam tuber group, nevertheless normal group was different significantly to the ulcer group. Based on the degree of stomach mucous structure damage, there was not significantly different (p>0,05) between cocoyam tuber group and aquadest group. Nevertheless, mice in the cocoyam tuber group had lower ulcer score than mice in the aquadest group. Therefore cocoyam tuber is safe consumed by the gastric ulcer mice. Cocoyam tuber is potential to develop as a functional food on gastric ulcer patient.